Leisure and housing consumption after retirement: new evidence on the life-cycle hypothesis - Miriam Beblo; Sven Schreiber (Review of Economics of the Household, 2021)
Foreseeable income reductions around retirement should not affect aggregate consumption. However, given higher leisure endowments after retirement, theory also predicts lower consumption of leisure substitutes. To avoid misinterpreting this predicted drop as a puzzle, our novel approach focuses on housing consumption (complementary to leisure in utility) and controls for leisure changes. In Germany tenants represent roughly half of all households, making many housing expenditures directly observable in micro data. We find significant negative impacts of the retirement status on housing consumption, which is hard to reconcile with life-cycle theory. Despite the lock-in nature of past housing decisions, income reductions at retirement have additional – though small – effects on housing.
Keywords: 330; D91 (Intertemporal Consumer Choice; Life Cycle Models and Saving); E21 (Consumption; Saving; Wealth); Consumption smoothing; Retirement-consumption puzzle; SOEP data; Housing decisions